U.S MILITARY INTERVENTION IN SYRIA: A NEO-REALIST APPROACH TO THE POWER STRUGGLE BETWEEN U.S AND RUSSIA - Khan, Taimur; Hussain , Dr Munawar (The journal of contemporary issues in business and government, 2022)
The main purpose of this research paper is a well examined study of US military engagement in Syria. It tries to assess the situation in Syria, where various domestic as well as foreign parties have joined in the civil war to protect or overthrow the regime of Bashar Al-Assad. Syria, thus, has been the center of power struggle between many international actors (notably the United States and Russia) which have competed in the strategy of supremacy in the most toughest and bloodiest version of Arab Spring in the Middle East. And they are Syrians and refugees who have been suffering in the civil conflict in which the U.S. and Russia's political and geo-strategic interests take center stage. With regard to the reasons, developments and results from these elements which are mainly part of the international relations agenda of the Syrian case, the theory of Neo-Realism has been applied to the situation, in order to better compare and contrast the different factors of the conflict. The case will thus be analyzed by focusing on the clashing Syrian policy interests between major powers such as U.S and Russia and their conception of alliances in Syria.